Microcrédito e empreendedorismo: alcance e limites dos programas de políticas públicas para população jovem do município de São Paulo - Simões, Luciano Schmitz (2014)
This research aims to discuss the reach of Entrepreneurship and Microcredit Brazilian public policies programs which might generates employment, work and income. In recent years, these mechanisms of public policies have been incorporated by Federal, State and local governments in order to be used as alternative tools for social inclusion, because of its ability to create work, employment and income. The starting point of this research are two studies conducted by us recently. The first study identifies the barriers faced by local governments, specifically, when trying to establish an effective relationship promoting a group organization and its entrepreneurial skills. From this evidence, was proposed a collective action among multilateral social agents (SEBRAE, NGOs, etc.), community and local government. This empirical research was developed with artisans in the City of Juiz de Fora, southeastern of Minas Gerais State, which was disjointed and has been showing no social representativeness. The result was the strengthening of this social group and the founding of the Artisans Association of Juiz de Fora city. The second study evaluates the effectiveness of social and economic development of the Heliopolis favela, in the city of São Paulo, throughout SPConfia, a city policy microcredit. The purpose of this study is to highlight the relationship between the microcredit institution and its assisted target, that uses this kind of resource to generate jobs and income. Both studies indicate that these policies aligned with its goals were developed for workers over 30 years old, which, somehow, had being already participating the formal labor market. Young people, in this case, does not integrate these programs. At the same time, these public programs neither have intention to qualify young people professionally for self-employment, nor trust enough credit to start up their own business. Therefore, the aim is to present the context in which the programs of public policies for entrepreneurship and microcredit offered by the city of São Paulo are structured and, then, better understand the reasons that creates a gap between government and university students.